The Influence of Intangible Assets, Financial Flexibility, and Human Capital on Sustainable Growth with Green Innovation as a Moderator - Purna, Putu Inten Citrawati; Werastuti, Desak Nyoman Sri; Adiputra, I Made Pradana (Dinasti Publisher, 2025)
This study, titled